1. EKSISTENSI KELOMPOK PEGIDA SERTA PROPAGANDA ANTI-PENCARI SUAKA DAN ISLAMOFOBIA DI JERMAN - Andi Arie Setya Ningrum; Reni Windiani; Sheiffi Puspapertiwi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
PEGIDA or Patriotische Europaer gegen die Islamisierung des Abendlandes is a patriotismgroup of European people against the Islamization of the West. Pegida spreads the antiasylum seeker and Islamophobia propagandas in Germany even in many Europeancountries. This research was conducted to determine the multiple factor that can influencethe existence of Pegida. The method of this research is qualitative with descriptive analysistype of research. The results of this research point out that in its movement Pegida spreadsthe hatred demeanor towards asylum seeker and Islam. The existence of Pegida werecaused by internal and external factors. The internal factors are the simillar of values,identity, norms, and language that are supporting the existence of Pegida. The externalfactors is Germany national regulation based on Constitution Republic Federal Germanyarticle 5, 8, dan 9 which ensure the protection of the freedom of expression, assembly, andassociation as the fundamental rights for every citizens.